2022
DOI: 10.1017/s1743923x22000083
|View full text |Cite
|
Sign up to set email alerts
|

Insecurity and Self-Esteem: Elucidating the Psychological Foundations of Negative Attitudes toward Women

Abstract: Political scientists recognize discriminatory attitudes as key to understanding a range of political preferences. Sexism is associated with both explicitly and non-explicitly gendered attitudes. But why do certain individuals display discriminatory attitudes, while others do not? Drawing from psychology, we examine the potential power of an underexplored set of personality traits—secure versus fragile self-esteem—in explaining gendered attitudes and preferences. With an online sample of (N = 487) U.S.-based pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…This research would suggest that those with low implicit self‐esteem might be especially sensitive to psychological threats, and one way to manage these threats can be political zeal and extremism. A more recent study by Mansell and Gatto (2022) also found that those showing a discrepancy between explicit and implicit self‐esteem were more likely to report hostile sexism, prefer men in leadership, and support former U.S. president Trump (and identify as Republican overall).…”
Section: Two Types Of Self‐evaluationmentioning
confidence: 94%
“…This research would suggest that those with low implicit self‐esteem might be especially sensitive to psychological threats, and one way to manage these threats can be political zeal and extremism. A more recent study by Mansell and Gatto (2022) also found that those showing a discrepancy between explicit and implicit self‐esteem were more likely to report hostile sexism, prefer men in leadership, and support former U.S. president Trump (and identify as Republican overall).…”
Section: Two Types Of Self‐evaluationmentioning
confidence: 94%
“…This could mean that male politicians can also suffer from stereotype-violation, albeit for a different associated trait. Given the prevalence of stereotype-based attacks against female politicians (Cassese and Holman 2018) and pervasive sexism (Cassese and Holman 2019;Mansell and Gatto 2022), however, I expect that stereotype violation has a more pronounced negative effects on evaluations of female than male representatives. To explore whether, and how, gender stereotypes affect candidate evaluations, I also examine whether the interaction effect between the gender of the politician and repositioning is determined by the personality traits perceptions of honesty, decisiveness, and competence.…”
Section: Expectationsmentioning
confidence: 99%
“…People can also use self-esteem to deal with adverse life events to reduce their effects. [ 11 ] According to Uruthirapathy and Dyke, self-esteem can be thought of as a set of thoughts, feelings, emotions, and experiences that shape the process of social life. [ 12 ] Self-esteem is one of the factors that affect one's compatibility in society.…”
Section: Introductionmentioning
confidence: 99%